The role of literature in group cultural identity: Constructing psychological belonging of rural communities through Chinese local literature - Yuqi Zhou (Environment and Social Psychology, 2025)
Based on group cultural identity theory and environmental psychology, this study employs a mixed-methods design to systematically analyze the mechanisms through which Chinese rural literature contributes to the construction of rural group psychological belonging. The research selected 95 classic rural literary works as textual corpus, combined with questionnaire surveys of 300 readers and in-depth interviews with 30 representative individuals. Using content analysis, thematic analysis, and statistical analysis methods, the study thoroughly explores the intrinsic connections between literary representation and group identity.The findings reveal: (1) Rural literature stimulates group cultural identity through multi-dimensional construction of environmental psychological imagery, with the emotional resonance index of natural environment descriptions reaching 4.8 points, and historical retrospective narratives showing an extremely strong positive correlation with collective memory intensity (r=0.856); (2) Character portrayal strengthens social role identification through archetypal significance and psychological projection, with typical character archetypes significantly correlating with readers' psychological identification (r=0.681), and kinship network density coefficient reaching 0.842; (3) Narrative discourse effectively delineates group psychological boundaries through strategies including dialect vernacular, value judgments, and narrative perspectives, with dialect usage density significantly correlating with group identity intensity (r=0.823); (4) Group identification mechanisms demonstrate three-dimensional integrated characteristics of cognition, emotion, and behavior, forming a complete identity construction system through environmental cognitive frameworks, emotional resonance stimulation, and behavioral norm guidance; (5) Literary representation and real-world psychology form a dynamic relationship of interactive construction, where literary works both reflect actual group psychology and exert an active constructive influence on group identity through cognitive schema shaping, emotional pattern guidance, and behavioral norm establishment. This research provides new theoretical perspectives for understanding the social psychological functions of literature and offers practical guidance for rural cultural construction and group identity cultivation.